Social Practices of Marginal Class Characters in Brian Khrisna's Novel Sisi Tergelap Surga According to Bourdieu's Perspective - Nova Rahma Dinna; Anas Ahmadi (Jurnal Pembelajaran Bahasa dan Sastra, 2026)
The novel "The Dark Side of Heaven," published by Gramedia Pustaka Utama (2023), tells a realistic and emotional story about the struggles of life on the outskirts of Jakarta. The book tells the story of 18 characters living behind the glitz and glamour of the capital, highlighting the dark side of poverty, betrayal, and hope. This study examines the social practices of marginalized class characters in the novel Sisi Tergelap Surga using Bourdieu’s perspective. This novel depicts the lives of marginalized class communities in the suburbs of Jakarta who are faced with economic limitations, social alienation, and the dominance of power structures that limit their space for movement. The purpose of this study is to describe the social practices of marginalized class characters influenced by habitus and capital ownership that can become survival strategies in the novel. This study uses Bourdieu’s sociology of literature approach. The research data sources are quotations from the novel Sisi Tergelap Surga by Brian Khrisna, published in 2023. The data collection technique was carried out through documentation, with data analysis using the Miles and Huberman flow model. The results of the study indicate that habitus and capital ownership are interrelated in shaping the social practices of marginalized class characters as survival strategies. Based on these results, it can be concluded that the social practices of marginalized class characters are formed through habitus and capital ownership in facing unbalanced social conditions.